Poverty, inequality and cancer - Solidoro Santisteban, Andrés (2010)
The greatest challenge for cáncer control in the 21st century is to reduce morbidity and mortality in developing countries ,in opinion of a number of leading authorities and cáncer institutions, because cáncer control in developing countries lags behind that in affluent countries. Cáncer is often considered to primarily affect people living in wealthy nations; this is a myth that needs to be corrected: six of the eleven million cases of cáncer registered in 2,008, and two thirds of the 7.6 million of cáncer related deaths occur in developing countries, and over the next 10 years, 70 per cent of cáncer cases will occur in the developing world.The vicious circle of the inefficacy in the use of our limited resources to treat advanced cáncer patients, and not implement the relatively inexpensive measures to the prevention and early detection of cáncer, ends with institutions with levels of excelency overwhelmed by the demand of attention for patients with advanced cáncer and for other side countries with a high proportion of poor uneducated, people with limited or none acces to the prevention and detection of curable precáncerous conditions. A well integrated primary care system that can offer prevention and detection of precáncerous conditions is the most efficient and cost-effective way of dealing with cáncer and to priorize when funding is limited.